European Tourist Perspective on Destination Satisfaction: Profiling tourists - Laureano, Raul M. S.; Vieira, Lisa (European Marketing Academy Conference - EMAC 2017, 2017)
For many years that tourism information has been collected and stored, but just few data is analysed in research to discover new patterns that increase the tourism knowledge. To extract knowledge about Europeans satisfaction and to identify demographic characteristic and travel behaviours of tourists that may discriminate the level of satisfaction with the destination and accommodation, data mining techniques are applied to the data from Flash Eurobarometer 414 “Preferences of Europeans towards tourism 2015”. Results show tourists present three levels of overall satisfaction while tourism organizations expect very satisfied tourists, being the only way to guarantee loyalty. Moreover, nationality of the tourist, by itself, is the characteristic more associated with satisfaction. The useful knowledge obtained enables tourism agencies to development marketing strategies according to the tourist profile and to ensure the development of promotional messages for products and experiences.